Competing crack initiation behaviors of a laser additively manufactured nickel-based superalloy in high and very high cycle fatigue regimes - Yang, Kun; Huang, Qi; Wang, Qingyuan; Chen, Qiang (International journal of fatigue, 2020)
•The separate S-N curves are firstly detected in additively manufactured metals.•Fatigue cracks originate from gas pores, lack of fusions, and columnar grains.•ΔK at the border of rough area corresponds to propagation threshold for long cracks.•Fatigue sensitivity of maximal micro-crack type, size, and location increase successively. Ultrasonic fatigue tests were performed to investigate high and very high cycle fatigue behaviors of a laser additively manufactured Inconel 718 (IN718) alloy in the as-deposited condition. The results indicate that the competition failure behavior between the surface and interior crack initiation results in the separate S-N curve. Both manufacturing defects (e.g., gas pore, lack of fusion) and columnar grains (matrix) observed in the microstructure could act as the original fatigue micro-cracks due to the effective restriction on manufacturing defects. The fatigue sensitivity levels increase successively in terms of the type, size, and location of the maximal micro-crack.